Prove that Tan-1 1/7 + Tan-1 1/13- tan-1 2/9=0
Answers
Answered by
0
Answer:
sttsustokstusoturastistlaro78tsop86soutaaiptauostuoiryasotu
Answered by
2
Considering L.H.S. tan-1 (1/7) + tan-1 (1/13) by, formula = tan-1 (20/90) = tan-1 (2/9) = R.H.S Hence, proved (ii) Given as sin-1 (12/13) + cos-1 (4/5) + tan-1 (63/16) = π Considering L.H.S. sin-1 (12/13) + cos-1(4/5) + tan-1(63/16) By, formula -63-16
Mark Me As Brainslist✔
Similar questions
Physics,
1 month ago
Geography,
2 months ago
Computer Science,
2 months ago
Geography,
10 months ago
Math,
10 months ago